Kompetensi Komunikasi dalam endidikan Dokter YangBerorientasi Pada kepentingan pasien:Belajar Dari Kasus Klinik dan Role -Play Mahasiswa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Communication competence in medical education usually focusing only on history taking, which is diseases oriented, while in the reality patients have their own perception of illness, feeling, hope, and expectation. The gap between patient and doctor may lead to uncooperative patient, which is in the end will not be an effective, neither efficient problem solving session for both. This study is aimed to explore more on the competency of patient centered communication style: the reason for encounter, empathy, and active listening, through study from clinical cases and result of student's role-plays during skills training sessions in Faculty of Medicine Gadjah Mada University. Furthermore, observing the importance of doctor-patient communication related with other competence of KIPDI III: managing